2021
DOI: 10.1016/j.brs.2020.12.010
|View full text |Cite
|
Sign up to set email alerts
|

tDCS-induced modulation of GABA concentration and dopamine release in the human brain: A combination study of magnetic resonance spectroscopy and positron emission tomography

Abstract: Background: Transcranial direct current stimulation (tDCS) to the dorsolateral prefrontal cortex (DLPFC) hypothetically modulates cognitive functions by facilitating or inhibiting neuronal activities chiefly in the cerebral cortex. The effect of tDCS in the deeper brain region, the basal ganglia-cortical circuit, remains unknown.Objective: To investigate the interaction between g-aminobutyric acid (GABA) concentrations and dopamine release following tDCS. Method: This study used a randomized, placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…This effect modulates cognitive functions. The last finding suggested tDCS also has an effect on deeper brain regions, for example, tDCS to the DLPFC modulates dopamine-GABA functions in the basal ganglia-cortical circuit (Bunai et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This effect modulates cognitive functions. The last finding suggested tDCS also has an effect on deeper brain regions, for example, tDCS to the DLPFC modulates dopamine-GABA functions in the basal ganglia-cortical circuit (Bunai et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also reported that dopaminergic treatment could prolong SP duration in patients with PD and suggested that SP may be modulated by the dopamine system (Nakashima et al, 1995). Furthermore, the recent study showed tDCS-induced dopamine release and GABA changes, which contributes to the phenomenon of SP (Bunai et al, 2021). Taking together, the beneficial motor effects of DLPFC tDCS may be related to dopamine release, therefore modulating the cortical inhibition in individuals with PD.…”
Section: Discussionmentioning
confidence: 83%
“…The prefrontal cortex is heavily regulated by dopamine and stimulation of frontal cortex may lead to an increase in extracellular dopamine concentrations (44). A recently published study demonstrated that stimulation of left DLPFC in healthy populations is associated with reduction of GABA in left DLPFC but also modulation of both GABA and dopamine in the striatum, demonstrating the effect of atDCS beyond the targeted cortical structures (45). Given the importance of corticostriatal activity in NF1 and other neuropsychiatric conditions, it will be important to determine in future studies whether stimulation of DLPFC has a modulatory effect on the neurotransmitters in the striatum.…”
Section: Discussionmentioning
confidence: 99%